Globalizing beauty : consumerism and body aesthetics in the twentieth century - Berghoff, Hartmut 1960- HerausgeberIn; Kühne, Thomas 1958- HerausgeberIn (Worlds of consumption, 2013)
Beauty matters. Throughout the world, more and more people from all walks of life spend time and money to make themselves beautiful because beauty expresses identity and shapes status and success. Whether white or black, male or female, young or old, gay or straight, working- or middle-class, Western or non-Western, democratic or fascist, people everywhere have adopted a central maxim of the twentieth century: everyone can be beautiful, and everyone should become beautiful. This volume tracks the historical roots and meanings of modern beauty cultures in the twentieth century, drawing on examples from Europe, North America, the Near East, Asia, and Africa